Knowledge sharing is knowledge transfer: a misconception in the literature - Tangaraja, Gangeswari; Mohd Rasdi, Roziah; Abu Samah, Bahaman; Ismail, Maimunah (Emerald Group Publishing, 2016)
Purpose: The paper aims to clearly differentiate knowledge sharing (KS) and knowledge transfer (KT) besides exemplifying their interconnections to minimize the current confusions in the knowledge management (KM) literature. Design/methodology/approach: An extensive literature review method was used to analyse relevant literature on both KS and KT to clearly delineate their differences and their interconnections. Findings: The paper found that KS is a subset of KT (using personalization strategy), whereas KT as a whole is a broader concept, if compared with KS. However, KS is not one of the immediate processes involved in KT (using codification strategy). The processes involved in KS and KT differ according to the strategy used (in KT) and perspective chosen (in KS). Other findings include KS (unidirectional) as reflective concept (viewed so far), whereas KS (bidirectional), KT (personalization) and KT (codification) as formative concepts. Research limitations/implications: The findings of this paper were based on the review of selected relevant articles only. Practical Implications: The paper will minimize the current confusions in the KM literature and will assist future researches on both KS and KT to ensure what these concepts entail to avoid construct underrepresentation. Originality/value: As compared to previous attempts, the present paper has shown the interconnections between KS and KT, as well as the differences based on the two perspectives of KS (unidirectional/bidirectional) and the two strategies of KT (personalization/codification), and such effort is new in the literature.